Introducing Physician Assistants to Ontario - Meredith Vanstone; Sarah Boesveld; Kristen Burrows (McMaster University Library Press, 2014)
In 2006, the Ontario Ministry of Health and Long-Term Care (MOHLTC) introduced Physician Assistants (PAs) through the announcement of demonstration projects, education and training programs, and subsequent funding. PAs are directly supervised by physicians and act as physician extenders by performing acts as delegated to them by their supervising physicians. PAs were proposed as a potential solution to help improve access to health care and reduce wait times throughout the province. Prior to the 2006 Ministry announcement, there was little public discussion regarding the acceptance of the PA role or its sustainability. Opposition from nursing and other groups emerged in response to the 2006 announcement and flared again when stakeholder comments were solicited in 2012 as part of the PA application for status as regulated health professionals. As a health reform, the introduction of PAs has neither succeeded nor failed. In 2013, the majority of PA funding continues to be provided by the MOHLTC, and it is unknown whether the PA role will be sustainable when the MOHTLC withdraws salary funding and health system employers must decide whether or not to continue employing PAs at their own expense.